SOSIALISASI PENGOLAHAN LIMBAH KULIT JERUK SEBAGAI ECO-ENZYME PADA MASYARAKAT DESA HAJIMENA, LAMPUNG SELATAN - Novian Riskiana Dewi; Triya Ferli Wulandari (Fakultas Sains dan Teknologi, 2023)
Waste is a residual material that holds no value if simply discarded. However, waste can become highly valuable if transformed into something beneficial. Just like orange peel waste, which can hold significant benefits if one knows how to process it. Therefore, a team of lecturers and students from UIN Raden Intan Lampung conducted a socialization on the processing of orange peel waste into eco-enzymes for the community of Hajimena Village, Lampung Selatan. The execution method of this community engagement activity employed a persuasive approach through dissemination and direct practice. The existence of this product has provided a solution to the previous problem, namely the lack of activities that produce products in the village. Currently, people are starting to realize the importance of managing organic waste so that it can be converted into high-value goods, avoiding littering which has the potential to pollute the environment. The activity was enthusiastically embraced by the people of Hajimena Village, Lampung Selatan, proceeded smoothly, and succeeded in producing plant fertilizer using easily accessible natural materials. Keywords: Socialization, Waste Processing, Orange Peel, Eco-Enzyme